2023
DOI: 10.1186/s41687-023-00600-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression trajectories during the COVID-19 pandemic: a secondary analysis of the impact of cognitive-appraisal processes

Abstract: Purpose This study characterized depression trajectories during the COVID pandemic and investigated how appraisal and changes in appraisal over time related to these depression trajectories. Methods This longitudinal study of the psychosocial impact of the COVID-19 pandemic included 771 people with data at three timepoints over 15.5 months. The depression index was validated using item-response-theory methods and receiver-operating-characteristic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…Many factors may play a role in this rising prevalence, including grief over the loss of loved ones (Eisma et al, 2021 ), social isolation (Pietrabissa and Simpson, 2020 ), and long-term symptoms of COVID-19 (Penninx, 2021 ), among others. In earlier research done by our group and on which the present study builds, we found that employment status was an important predictor of depression (Schwartz et al, 2023a , b ). Specifically, people who were disabled from work due to a medical condition were more likely to be depressed throughout the pandemic than other employment groups (Schwartz et al, 2023a , b ).…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Many factors may play a role in this rising prevalence, including grief over the loss of loved ones (Eisma et al, 2021 ), social isolation (Pietrabissa and Simpson, 2020 ), and long-term symptoms of COVID-19 (Penninx, 2021 ), among others. In earlier research done by our group and on which the present study builds, we found that employment status was an important predictor of depression (Schwartz et al, 2023a , b ). Specifically, people who were disabled from work due to a medical condition were more likely to be depressed throughout the pandemic than other employment groups (Schwartz et al, 2023a , b ).…”
Section: Introductionsupporting
confidence: 62%
“…In earlier research done by our group and on which the present study builds, we found that employment status was an important predictor of depression (Schwartz et al, 2023a , b ). Specifically, people who were disabled from work due to a medical condition were more likely to be depressed throughout the pandemic than other employment groups (Schwartz et al, 2023a , b ). Even after adjusting the longitudinal models for COVID-19-specific stressors (e.g., hardship, worry, and low social support) and cognitive appraisal processes, the association between being disabled and being depressed remained highly significant (Schwartz et al, 2023b ).…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In this long research path, cognitive-appraisal processes were documented to explain substantial variance in a wide range of patient samples [ 21 ], and to help to explain why two individuals in identical health states rate their QOL differently [ 22 ]. Appraisal assessment helps to identify and explain how contextual and psychological factors matter in patients’ subjective evaluation of their physical and emotional health [ 21 , 22 , 23 ]. With this growth in the evidence base for appraisal, there has also been increasing parsimony in appraisal assessment [ 20 ] and in statistical methods for working with appraisal [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appraisal assessment helps to identify and explain how contextual and psychological factors matter in patients’ subjective evaluation of their physical and emotional health [ 21 , 22 , 23 ]. With this growth in the evidence base for appraisal, there has also been increasing parsimony in appraisal assessment [ 20 ] and in statistical methods for working with appraisal [ 23 ]. These statistical methods have relied on data reduction and relatively complex multivariate analyses which, though useful for summarizing findings at the aggregate level, may also make the findings hard to parse for clinicians and others not familiar with complex statistical modeling.…”
Section: Introductionmentioning
confidence: 99%